2020
DOI: 10.1101/2020.04.17.047654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image-based elastography of heterochromatin and euchromatin domains in the deforming cell nucleus

Abstract: Chromatin of the eukaryotic cell nucleus comprises of microscopically dense heterochromatin and loosely packed euchromatin domains, each with distinct transcriptional ability and roles in cellular mechanotransduction. While recent methods have been developed to characterize the nucleus, measurement of intranuclear mechanics remains largely unknown. Here, we describe the development of nuclear elastography, which combines microscopic imaging and computational modeling to quantify the relative elasticity of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Although senolityc, epigenetic, and cytoskeleton-interfering drugs represent a promising and novel therapeutic approach, it is necessary to proceed with a deeper understanding of the molecular pathways, potentially establishing the tight association between cell-based mechano-sensing and cellular senescence. Novel interdisciplinary approaches integrating measurements of the forces actually developed by the cells [ 85 ] along with determination of the nuclear topology [ 86 ] and chromatin rheological features [ 87 ] will open novel avenues to resolve the problem of cellular senescence and retard the onset of aging-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although senolityc, epigenetic, and cytoskeleton-interfering drugs represent a promising and novel therapeutic approach, it is necessary to proceed with a deeper understanding of the molecular pathways, potentially establishing the tight association between cell-based mechano-sensing and cellular senescence. Novel interdisciplinary approaches integrating measurements of the forces actually developed by the cells [ 85 ] along with determination of the nuclear topology [ 86 ] and chromatin rheological features [ 87 ] will open novel avenues to resolve the problem of cellular senescence and retard the onset of aging-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study using isolated nuclei from HeLa cells demonstrated that in nuclei stretched at a physiologically relevant speed of 50 nm/s, lamin A/C levels modulate the nuclear stiffness primarily in response to more than 3 µm of stretch, whereas euchromatin/heterochromatin levels mainly control nuclear stiffening at less than 3 µm stretch (Stephens et al, 2017). Moreover, disruption of the LINC complex abrogates the difference between heterochromatin and euchromatin elasticities/stiffnesses at the peak nuclear deformation induced by CM contraction (Ghosh et al, 2021), suggesting that an intact LINC complex is also necessary for maintaining chromatin stiffness. Chromatin decondensation further results in an increased movement of chromatin, while inhibition of myosin II and decoupling the nucleus from the cytoskeleton decreases chromatin mobility in HUVEC cells (Spagnol and Noel Dahl, 2014), further supporting the notion that the intact actomyosin apparatus and the LINC complex are critical factors for the mechanical signal transmission to chromatin.…”
Section: Influence Of Mechanical Forces On Nuclear Morphology Chromatin Organization and Gene Transcriptionmentioning
confidence: 99%
“…Optical microscopy-based [170][171][172] elastography is a powerful potential method to measure the distribution of mechanical properties noninvasively within the nucleus. Based on techniques like deformable image registration and inverse finite element methods, image-based elastography of heterochromatin and euchromatin domains in the deforming cell nucleus is now possible [173,174].…”
Section: Intranuclear Stiffnessmentioning
confidence: 99%